2016
DOI: 10.1002/aenm.201600918
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Nanowires and Lithium Cobalt Oxide Nanowires in Graphene Nanoribbon Papers for Full Lithium Ion Battery

Abstract: a few examples have attained small increments of capacity or higher voltage operation >5 V versus Li/Li + . [5][6][7] An exception is sulfur, which has an outstanding capacity of 1675 mA h g −1 , but a lower voltage of operation of 2.1 V. [8] On the other hand, several high capacity alternatives, such as Li metal, Si, and other alloying metals (Sn, Sb, Al) are possible in anode applications. [9] This higher capacity can decrease the total amount of anode mass necessary to compose the batteries, increasing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 44 publications
0
54
0
Order By: Relevance
“…5f (see calculations and literatures in Supplementary Table 6−7). 9,[32][33][34]36 This plot shows that our high-C/A full-cells delivered much higher ESP (up to 401 Wh kg -1 ) than any other reports (<261 Wh kg -1 , open symbols), highlighting their superlative performance. We note that, after calendaring to increase the density of both electrodes by ~60% and so decrease electrolyte mass, we could increase the energy density up to 480 Wh kg -1 , a value which is nearly twice the state-of-the-art (see Supplementary Table 7).…”
Section: Full-cell Performancementioning
confidence: 63%
See 2 more Smart Citations
“…5f (see calculations and literatures in Supplementary Table 6−7). 9,[32][33][34]36 This plot shows that our high-C/A full-cells delivered much higher ESP (up to 401 Wh kg -1 ) than any other reports (<261 Wh kg -1 , open symbols), highlighting their superlative performance. We note that, after calendaring to increase the density of both electrodes by ~60% and so decrease electrolyte mass, we could increase the energy density up to 480 Wh kg -1 , a value which is nearly twice the state-of-the-art (see Supplementary Table 7).…”
Section: Full-cell Performancementioning
confidence: 63%
“…Standard additives such as carbon black (CB) yield low, inhomogeneous and unstable electrode conductivity, [3][4][5] limiting electrochemical performance, especially for very thick electrodes. 6 While a number of methods have been suggested to maximize C/A, [7][8][9][10][11][12][13][14][15][16] none are scalable. We aim to develop a general, materials science-based strategy that allows the production of very thick electrodes which retain almost all of their theoretical capabilities.…”
Section: Density For Both Anodes and Cathodes // Sp C A C M A mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the aspect ratio of the nanowires has an important influence on the physical properties of the freestanding stacked nanowires papers. It is reported that nanowires of a larger aspect ratio result in nanowire papers of higher free volume fraction so that higher mass loading of the active materials can be enabled . Durstock and co‐workers reported an assembly consisting of interconnect Ni nanofibers of diameters of 100–1000 nm ( Figure a) .…”
Section: D Metal Current Collectorsmentioning
confidence: 99%
“…Salvatierra et al prepared a free‐standing nanocomposite paper of porous Si‐NWs and graphene nanoribbons (GNRs) by a cofiltration method . The interconnected Si‐NWs and GNRs formed a stable conductive path across the paper, which made it more robust and flexible.…”
Section: Si For Libsmentioning
confidence: 99%